2014
DOI: 10.1002/jat.3036
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between chemical‐induced kidney weight increases and kidney histopathology in rats

Abstract: The kidney is a major site of chemical excretion, which results in its propensity to exhibit chemically-induced toxicological effects at a higher rate than most other organs. Although the kidneys are often weighed in animal toxicity studies, the manner in which these kidney weight measurements are interpreted and the value of this information in predicting renal damage remains controversial. In this study we sought to determine whether a relationship exists between chemically-induced kidney weight changes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 11 publications
2
16
0
1
Order By: Relevance
“…2017c). However, change in absolute kidney weight, but not kidney-to-BW ratio, is an accepted predictor of kidney histopathology in subchronic and chronic studies (Craig et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
“…2017c). However, change in absolute kidney weight, but not kidney-to-BW ratio, is an accepted predictor of kidney histopathology in subchronic and chronic studies (Craig et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular note was the finding that the AUC 0-12h of TCVC, which may be metabolically activated to electrophilic, cytotoxic, genotoxic, and/or mutagenic intermediates, was approximately 30%-40% lower in the kidneys of mice with NAFLD compared with LFD-fed mice. Biochemical and Histopathological Evaluation of Kidney Injury Absolute kidney weight, but not kidney-to-bodyweight ratio, has been shown to correlate strongly with sub-chronic and chronic renal injury in rats (Craig et al, 2015). Absolute kidney weight was unaffected by diet or PERC exposure (Table 1); however, kidney-to-body weight ratio was decreased in HFD-fed mice compared with LFD-fed control, and was significantly increased by PERC exposure in all three diet groups.…”
Section: Nafld Affects the Toxicokinetics Of Perc And Its Oxidative And Conjugative Metabolitesmentioning
confidence: 95%
“…The results of glomerular diameter measurements were in the normal range and necrosis has not occurred, so the kidney weight in albino rats is also normal. Craig et al (2015) reported kidney weight correlation with kidney histopathology. According to Rasch & Dørup (1997), diabetic rats can increase kidney weight by 53 -93%.…”
Section: Resultsmentioning
confidence: 99%